Pengembangan Multimedia Pembelajaran Dengan Aplikasi Lectora Inspire Pada Materi Bumi Sebagai Ruang Kehidupan di Kelas X SMA Negeri 5 Surakarta - Azidatul Khairatin Nu'mah; Djoko Subandriyo; Singgih Prihadi (GEADIDAKTIKA, 2022)
The aim of this research are to knows (1) To determine the feasibility of developing multimedia learning applications for Lectora Inspire on earth material as a space of life in class X IPS SMA N 5 Surakarta. (2) Knowing the effectiveness of multimedia learning Lectora Inspire applications on the material of the earth as a space of life after being implemented in class X IPS SMA N 5 Surakarta.The research method used in this research is the research and development method with ADDIE development models namely Analyze, Design, Development, Evaluation and Implementation. Data collection techniques with interviews, questionnaires, tests and documentation. Data analysis techniques with multimedia feasibility analysis of the questionnaire by the validator and calculation of effectiveness with the T test with a confidence level of 5% of the data that has been calculated with the normality test.Based on data analysis, the results of the research are known as follows: (1) Multimedia learning of Lectora Inspire applications on the material Earth as Life Space in class X SMA N 5 Surakarta is feasible to use by obtaining a value of 5 (very feasible) based on the results of validation. (2) Multimedia learning application of Lectora Inspire on the material of Earth as Life Space in class X SMA N 5 Surakarta is effective to be used in the learning process based on the T Test to obtain the results of Sig. (2-tailed) is 0,000 so less than 0.05 then Ho is rejected and Ha is accepted. Keywords : Development of Learning Multimedia, Lectora Inspire, ADDIE, Earth as Life Space.